Bring the state (information) in: Campaign dynamics in the run-up to a German referendum. (June 2015) - Faas, Thorsten
Abstract: This article analyses exposure to different sources of campaign information, and their effects on citizens' feeling of being informed about referendums. The analysis is based on an innovative rolling panel study that allows for a rigorous tracking of campaign dynamics in the run-up to the referendum. Using a referendum on a large-scale infrastructure project in the German state of Baden-Württemberg, empirical findings show that official information provided by the government had the greatest effect in reaching citizens and also had the strongest impact on their feeling of being informed. The article demonstrates that the state plays a crucial role in providing an appropriate information environment prior to a referendum.